Tracer Study STKIP Alumni Andi Matappa - Rahmat Kamaruddin, Firdha Razak, (Global Science Education Journal, 2019)
This research was conducted with the aim of: 1) Exploring information from alumni regarding the development of competencies needed by the job market for curriculum improvement materials; 2) Searching for workplaces, occupations, waiting times for getting a job, first salary, current job, and other information from STKIP alumni Andi Matappa. The Tracer Study design uses a sensal survey that is the target population of the study is the entire population of the 2017 graduate cohort with 100 graduates of which 58 are from the Guidance and Counseling study program and 42 from the Mathematics Education study program. The data collection method that will be used is the online method using QTAFI (Question Table and Figure) software, telephone interviews, social media and email tracking. The instrument used was a standardized completely adapted Indotrace questionnaire that included questions listed in the Kemristekdikti Tracer Study Online questionnaire. The results showed that alumni need an average of 1 (one) month to get their first job after graduation and the three highest ways to obtain it through relationships, the internet and CDC / career center. As many as 44.3% of STKIP alumni Andi Matappa work as educators in government agencies and 36.7% work in private companies. The majority of graduates have worked in accordance with the field of study undertaken during the study period, but need to be strengthened in several ways, especially in foreign language and computer skills so that graduates can work in accordance with the development of Science and Technology.